Bentuk dan posisi kondilus sebagai marker pada Temporomandibular Disorder (TMD) melalui radiografi panoramik - Khamila Gayatri Anjani; Aga Satria Nurrachman; Fadhlil Ulum Abdul Rahman; Ria Noerianingsih Firman (Ikatan Radiologi Kedokteran Gigi Indonesia, 2020)
Objectives: The purpose of writing this literature review is to describe the condyle shape and position parameters in panoramic radiographs to be used as markers in diagnosing a TMD case. Literature Review: There are several classifications of both normal and pathological condyles in terms of panoramic radiographs, however these require more detailed observation. Panoramic radiographs that are only two-dimentional and only performed when the teeth are biting edge to edge so that they only show the position of the condyle movement and the shape of the condyle from the lateral view. Panoramic radiograph also have limitations in imaging soft tissues such as articular disc which are vital anatomy in analyzing a TMD case. Conclusion: Assessment of the shape and position of the condyles on a panoramic radiograph can be used as an early diagnosis of TMD. 2-dimensional modalities such as TMJ conventional lateral and frontal or 3-dimensional modalities such as CBCT or CT can be used for further assessment of a TMD case, while MRI or ultrasound can be used for soft tissue abnormalities.